MATEC Web of Conferences - Voloshko, I. (EDP Sciences, 2018)
The results of temperature measurements in model rooms of a closed type with a system of radiant heating are presented. The temperatures of different designs' surfaces in large-sized rooms, heated by a gas infrared emitter of light type, are established. Conclusions are drawn about the mechanism of the medium's heating, depending on the conditions of heat exchange, and also on providing worker's comfortable working conditions, when the medium is heated by a gas infrared emitter.